Intelligent Engine Health Monitoring System for Enhanced Vehicle Performance - Yogita Dubey; Khushal Damahe; Usha Ambule; Sanskruti Alone; Tanaya Deshpande; Roshan Umate (Journal of Machine Engineering)
In traditional vehicle maintenance, there’s often no real-time data available, leaving drivers in the dark about important health and safety parameters. This gap can cause problems like low oil levels, poor oil quality, and overheating, which can put the vehicle and passengers at risk. This paper presents the intelligent engine health monitoring system for enhanced vehicle performance. The system uses ESP8266, ultrasonic sensor, light dependent resistor (LDR), and DS18B20 temperature sensors for continuous monitoring of the oil level, oil quality assessment, and engine temperature measurement in real-time. Oil quality assessment using RGB and white light transmission through a glass tube is proposed with improved accuracy in degradation detection. Blynk app interface in the proposed system produces the instant alert for exceeding threshold limit of sensor to ensures enhanced vehicle performance. Results demonstrate that blue light detects early-stage oil degradation, green light provides a balanced evaluation, and red light identifies severe degradation. A comparative analysis with optical color sensors and ultrasonic-based oil detection highlights the system's higher adaptability and real-time monitoring capabilities.